The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1038/sc.2015.179
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and socioeconomic status, complications and quality of life in people with spinal cord injuries after discharge from hospital in Bangladesh: a cohort study

Abstract: Study design: Mixed retrospective-prospective cohort study. Objectives: To determine psychological and socioeconomic status, complications and quality of life in people with spinal cord injuries (SCI) after discharge from a hospital in Bangladesh. Setting: Bangladesh. Methods: All patients admitted in 2011 with a recent SCI to a hospital in Bangladesh were identified. Patients were interviewed by telephone in 2014 using translated versions of the SF12, the SCI Secondary Conditions Scale, the Centre for Epidemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 15 publications
(17 reference statements)
3
38
0
Order By: Relevance
“…It is natural that, when those with a complete motor lesion were compared with those with an incomplete lesion, a complete lesion was associated with more difficulties in getting around and self-care. In our study, inability to walk was correlated with other impairments (getting around, self-care, participation and cognition) as in previous studies, which found wheelchair-dependency (36,37) and mobility restrictions (17) to increase difficulties in other domains of participation (17,37) and to decrease quality of life (36). Also, current employment was found to be associated with other domains (mobility, self-care, and life activities) in our study population.…”
Section: Discussionsupporting
confidence: 86%
“…It is natural that, when those with a complete motor lesion were compared with those with an incomplete lesion, a complete lesion was associated with more difficulties in getting around and self-care. In our study, inability to walk was correlated with other impairments (getting around, self-care, participation and cognition) as in previous studies, which found wheelchair-dependency (36,37) and mobility restrictions (17) to increase difficulties in other domains of participation (17,37) and to decrease quality of life (36). Also, current employment was found to be associated with other domains (mobility, self-care, and life activities) in our study population.…”
Section: Discussionsupporting
confidence: 86%
“…This lack of protection against climate change is especially true for those persons with SCI living in underdeveloped countries. Thus, increases in global temperature may further challenge decentralized thermoregulatory mechanisms and expose the vulnerability of persons with SCI to hyperthermia and challenge survival when attempting to cope with prolonged heat exposure [42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…In spite of a promising political environment for people with disabilities, research still indicates that many people with spinal cord injury (often wheelchair users) in Bangladesh rarely leave their homes, have reduced opportunities for employment, experience poverty, and have secondary conditions such as pressure ulcers (Hossain et al, 2016). Additionally, evidence demonstrates that people with spinal cord injury in Bangladesh report low total community integration and life satisfaction (Ahmed et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, evidence demonstrates that people with spinal cord injury in Bangladesh report low total community integration and life satisfaction (Ahmed et al, 2017). Researchers have also indicated that people with spinal cord injury, many of whom use wheelchairs, have moderate rates of depression and report limited quality of life (Hossain et al, 2016) as well as lower self-efficacy (which has been linked to depression) (Villanueva et al, 2017). In the light of this situation, there is a necessity for better identification of barriers in the hope that policy-makers and service providers may then direct their attention to facilitate effective interventions and improve the quality of life for this population (Hossain et al, 2016;Ahmed et al, 2017).…”
Section: Introductionmentioning
confidence: 99%